EFFECT OF FOOTBALL ON REHABILITATION OF ANKLE INJURY PATIENTS - Liu,Jie (2022)
ABSTRACT Introduction: Brief introduction: Ankle tendon and ligament sports injuries are common in football players. Objective: To continue to improve special strength training related to the characteristics of football after rehabilitation of injured ankle tendons and ligaments. Methods: Two master football sportsmen were rehabilitated by multi-point equal-length, short-arc and long-arc equal-speed training combined with balance ability exercises. Results: There were two long muscle L be maintain muscle tone plantar flexors force four times of 96 n/m, n/m 121, 140 n/m, 145 n/m than back flexors force of 63 n/m, 52 n/m, 60 n/m, 74 n/m tall. Plantar flexor fatigue was 57%, 30%, 29%, 12%, 28%, 18%, 20%, 21%. Conclusions: With the passing of time, the relative peak moment value of the right ankle plantar flexor muscle group of the two patients kept rising, the dorsiflexor muscle was basically flat, and the work fatigue index decreased step by step, indicating that the right ankle muscle strength level was significantly improved, the anti-fatigue ability was improved, and the rehabilitation treatment had a good effect. Level of evidence II; Therapeutic studies - investigation of treatment results.